Impact of A1 Asymmetry on the Woven EndoBridge Device in Anterior Communicating Artery Aneurysms - Cortese, J.; Caroff, J.; Girot, J.-B.; Mihalea, C.; Da Ros, V.; Aguiar, G.; Elawady, A.; Ikka, L.; Gallas, S.; Ozanne, A.; Chalumeau, V.; Rouchaud, A.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Woven EndoBridge (WEB) devices are increasingly used to treat intracranial aneurysms. A1 asymmetry contributes to anterior communicating artery aneurysm formation and to treatment instability after coiling. We sought to evaluate whether A1 asymmetry had an impact on angiographic outcome in anterior communicating artery aneurysms treated with the WEB.MATERIALS AND METHODS: Anterior communicating artery aneurysms treated between July 2012 and July 2020 with the WEB from an institutional review board–approved database were reviewed. A1 asymmetry was categorized as the following: absence of the A1 segment on 1 side (unilateral A1) versus bilateral A1. Univariate and multivariable analyses assessed independent predictors of adequate (WEB Occlusion Scale A, B, and C) and complete occlusion (WEB Occlusion Scale A and B).RESULTS: Forty-eight individual aneurysms (47 patients) were included in the final analysis, of which 16 (33%) were acutely ruptured. The mean size was 6.5 (SD, 2.2) mm. Adequate and complete occlusion was achieved in 33 (69%) and 30 (63%) cases, respectively. Unilateral A1 was associated with significantly higher rates of adequate (92% versus 60% for bilateral A1; P = .03) and complete occlusion (92% versus 50% for bilateral A1; P < .01). Multivariable logistic regression confirmed unilateral A1 as an independent predictor of both adequate (OR = 10.6; 95% CI, 1.6–220.7; P = .04) and complete occlusion (OR = 9.5, 95% CI, 1.5–190.2; P = .04. A sensitivity analysis comparing unilateral “functional” A1 with bilateral “functional” A1 showed similar results. WEB shape modification was not influenced by the unilateral A1 configuration (P = .70).CONCLUSIONS: Anterior communicating artery aneurysms with a unilateral A1 configuration treated with WEB devices are associated with better angiographic outcome than those with bilateral A1. This finding supports the hypothesis that WEB devices are resistant to unilateral flow in the aneurysm as opposed to coils.ACoAanterior communicating arteryWOSWEB Occlusion ScaleWShMWEB shape modification